2005
DOI: 10.1001/archpedi.159.6.536
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Correct and Consistent Condom Use on Chlamydial and Gonococcal Infection Among Urban Adolescents

Abstract: Our findings indicate that assessing both correctness and consistency of use is important for evaluation of condom effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 40 publications
3
56
1
1
Order By: Relevance
“…43,190 Consistent evidence supports condoms as reducing the risk of disease transmitted to and from the penile urethra, including gonorrhea, Chlamydia, trichomoniasis, hepatitis B, and HIV. [191][192][193][194][195] Emerging evidence also supports condoms as reducing the risk of acquiring diseases transmitted through skin or mucosal contact, including genital herpes simplex virus, 196,197 human papillomavirus, 198,199 and syphilis. 200 Because condoms protect against STIs, all sexually active adolescents should be encouraged to use condoms, regardless of whether an additional contraceptive method is used.…”
Section: Male Condomsmentioning
confidence: 99%
“…43,190 Consistent evidence supports condoms as reducing the risk of disease transmitted to and from the penile urethra, including gonorrhea, Chlamydia, trichomoniasis, hepatitis B, and HIV. [191][192][193][194][195] Emerging evidence also supports condoms as reducing the risk of acquiring diseases transmitted through skin or mucosal contact, including genital herpes simplex virus, 196,197 human papillomavirus, 198,199 and syphilis. 200 Because condoms protect against STIs, all sexually active adolescents should be encouraged to use condoms, regardless of whether an additional contraceptive method is used.…”
Section: Male Condomsmentioning
confidence: 99%
“…1 Advantages include male involvement in the responsibility for contraception, easy accessibility by minors without a prescription, and low cost. Latex condoms also reduce STI transmission, with consistent evidence for the reduction of gonorrhea, chlamydia, trichomoniasis, [119][120][121][122][123] and hepatitis B and HIV transmission 124 and emerging evidence for the reduction of herpes simplex virus, 125,126 human papillomavirus, 127,128 and syphilis transmission. 129 However, condom use requires commitment at every sex act, tends to drop off over time, and is influenced by individual, relationship, and broader social factors.…”
Section: Male Condomsmentioning
confidence: 99%
“…(9,11,14) However, this study found that young adults take less risks when engaging in sexual intercourse away from home, with higher levels of condom use and lower levels of delayed application. These findings are novel, highlighting the importance of context when trying to understand intentional user errors, such as the late application of condoms.…”
Section: Consistent With International Literature Late Application Ofmentioning
confidence: 57%
“…The late or delayed application of a condom, an intentional user error, is a relatively common behaviour (5)(6)(7)(8) compromising the protective effects of condoms. (9) Despite the prevalence of late application it is unclear why people who are obviously motivated to use a condom do not do so from the time of initial penetration. This is due, in part, to a reliance on summary measures of condom use error in the literature, combining either intentional errors (late application and early removal) and non-intentional errors (condom breakage, slippage or leakage), (5,(9)(10) or intentional errors alone as an indicator of incomplete condom use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation